"On s'occupe du multiple, on tourne le dos à l'unité": Ying Chen and Nomadic Figurations of the Subject. (June 2015) - Rodgers, Julie
Abstract : This article employs Rosi Braidotti's nomadic theory to offer a new theoretical reading of Ying Chen's fiction. The article demonstrates how nomadic theory provides us with the tools to understand Chen's complex vision of subjectivity as one that defies unity, fixity, and coherence of any sort. Instead, Chen presents us with a figuration of the self that reflects the velocity and constant fluctuations of the twenty-first-century postmodern, or, indeed, posthuman society that we inhabit. Just like Braidotti's nomadic vision of existence, Chen's fiction explodes boundaries and challenges traditional views of the self.